Misoprostol Use vs Foley Catheter for Cervical Preparation before Surgical Management of Late Miscarriage - Umm E Kalsoom; Zeb, Tahira; Spogmai; Wazir, Nighat Aziz (Indus Journal of Bioscience Research, 2025)
Objective: To compare the effectiveness of misoprostol and Foley catheter for cervical preparation before surgical management of late miscarriage, specifically evaluating the time to cervical dilation, surgical duration, and complication rates. Methodology: A retrospective study was conducted at Hayatabad Medical Complex, Peshawar, from October 2024 to March 2024, including 100 patients (50 in each group). The study analyzed demographic data, time to cervical dilation, surgical duration, and complications for both methods. Statistical analysis was performed using independent t-tests to compare the groups, with p-values of less than 0.05 considered significant. Results: The average time to cervical dilation for the misoprostol group was 6.5 hours (±2.1 hours), while the Foley catheter group had a mean time of 9.2 hours (±3.3 hours), with a statistically significant difference (p=0.022). Surgical duration was 37.8 minutes (±9.5 minutes) for misoprostol and 41.2 minutes (±10.3 minutes) for Foley catheter, with no significant difference (p=0.134). Complications were similar across both groups, with uterine hyperstimulation more common in the misoprostol group and cervical lacerations more frequent in the Foley catheter group. Conclusion: Misoprostol provides a faster time to cervical dilation compared to the Foley catheter, though both methods are safe and effective. This study supports the use of misoprostol for quicker cervical preparation, with recommendations for further research on combined methods and long-term outcomes.